Acute myocarditis during adjuvant therapies for breast cancer: a case report - Yumiko Ushiyama; Yoshiya Horimoto; Toshitaka Uomori; Yumiko Ishizuka; Misato Okazaki; Hiroko Onagi; Takuo Hayashi; Junichiro Watanabe; Mitsue Saito (Surgical Case Reports)
Abstract Background With the improvement of optimal perioperative drug therapy for breast cancer patients, physicians now have to treat the adverse effects and comorbidities associated with long-term treatments. We report a case who suffered cardiac arrest due to acute myocarditis developed after initiation of adjuvant treatment. Case presentation After completing preoperative chemotherapy and undergoing curative surgery for right breast cancer, a 46-year-old female patient started adjuvant tamoxifen and resumed trastuzumab. Two months later, she complained fever and dyspnea. Blood tests showed a marked increase in hepatic enzymes, and the patient was rushed to our emergency room on suspicion of drug-induced liver injury. In the emergency room, the patient went into cardiac arrest shortly after tachycardia with ST-segment elevation appeared on the monitored electrocardiogram. Resuscitation was started immediately and tracheal intubation, intra-aortic balloon pumping, and extracorporeal membrane oxygenation were started. Coronary angiography results were negative for ischemic heart disease. A diagnosis of fulminant myocarditis was made and steroid pulse therapy and immunoglobulin therapy were started. After the start of treatment, the symptoms of heart failure improved steadily and the patient was discharged on the 28th day. Histological findings of the myocardial biopsy revealed degeneration and necrosis of myocardial cells with marked lymphocytic infiltration, consistent with the histology of lymphocytic myocarditis. Serum cytomegalovirus, coxsackie B virus and adenovirus antibodies were all elevated and these findings were consistent with acute viral myocarditis. Conclusions We report a case with strong indications for therapy-induced liver damage, who was ultimately diagnosed with acute viral myocarditis and successfully treated with multidisciplinary therapy. We believe that our findings would be useful for other clinicians in managing similar patients.